PENGARUH INSENTIF TERHADAP MOTIVASI KERJA KARYAWAN MATAHARI DEPARTMENT STORE ARTOS MAGELANG (MOTIVASI, 2022)
Purpose. This research is a type of quantitative research with the title "The Effect of Incentives on Employee Work Motivation (Matahari Department Store Artos Magelang)". This research was conducted to find out how the influence of financial incentives and non-financial incentives on the work motivation of Matahari Department Store Artos Magelang employees and to find out which variables affect work motivation.Design/methodology. The analytical tool in this study is Multiple Regression Analysis, which is to find out the significant influence between financial and non-financial incentives on employee work motivation through the F test and T test, to find out which variable has a stronger influence using the partial correlation value (r). Then to test the questionnaire, used validity and reliability tests. The results of the instrument test in this study regarding the variables of Financial Incentives, Non-Financial Incentives and Work Motivation were declared valid and reliable.Findings. Based on the results of multiple linear regression analysis Financial Incentives have no significant effect on employee work motivation but Non-Financial Incentives have a significant effect on employee work motivation. So the company should be able to provide a clear program on how to achieve the targets set by management, and remain consistent in providing non-financial incentives.